Potensi Dasar Individu Muslim Sebagai Penunjang Kehadiran Diri Dalam Peran Khalifatullah dan ‘Abdullah - Vera, Susanti; Zulaiha, Eni; Yunus, Badruzzaman M (Jaqfi: Jurnal Aqidah dan Filsafat Islam, 2022)
Humans as creatures who have the title "the best form" is an affirmation of Allah SWT that He has created and made a complete spiritual and physical form. This event indicates that humans have basic potential that continues to develop biologically as well as their knowledge, so that humans are given the mandate to carry out two roles as well as the purpose of their presence, namely as khalifatullah and 'Abdullah on earth. However, the orientation of a Muslim's life is currently being hit by the development of a life style that follows trends and the pace of the times which results in the mingling of global ideologies, so that the basic human potential is no longer directed to achieving the essence of his presence as the representative of Allah (khalifatullah) and the servant of Allah ('Abdullah) in the world. earth. Thus, a study of basic human potential and how to develop it is needed in the order of life and human life. The purpose of this study is to discuss the basic potential of Muslim individuals in the Qur'an as a supporter of carrying out their roles as khalifatullah and 'abdullah on earth. This study applies a qualitative step. This research approach is human axiological aspect. The results and discussion of this research include the definition of human potential in the Qur'an, basic potential as eternal existence, and procedures for maximizing potential so that it can support the role of both humans as khalifatullah and 'abdullah. The conclusion of this study is that there are six approaches that are considered capable of activating human potential, in order to achieve awareness of the role and purpose of presence in this universal reality, namely social, moral, philosophical, chronological, meditation, and functional approaches.